2D graphdiyne: an excellent ultraviolet nonlinear absorption material. Issue 11 (9th March 2020) - Zhang, Fang; Liu, Guowei; Yuan, Junjie; Wang, Zhengping; Tang, Tianhong; Fu, Shenggui; Zhang, Huanian; Man, Zhongsheng; Xing, Fei; Xu, Xinguang
Abstract : GDY is veritable ultraviolet OL material, which has potential applications in ultraviolet optics. Abstract : With an sp 2 -hybridized carbon atom structure, graphene is recognized as a nonlinear absorption (NLA) material, which has motivated scientists to explore new allotropes of carbon. Different from graphene, graphdiyne (GDY) consists of sp- and sp 2 -hybridized carbon atoms. An sp-hybridized carbon–carbon triple bond structure will bring in novel nonlinear optical properties, which are different from other allotropes of carbon. In this study, we investigated the broadband NLA properties (ultraviolet–infrared waveband) of GDY nanosheets, exfoliated using a liquid-phase exfoliation (LPE) method. The short ultraviolet cut-off wavelength (around 200 nm–220 nm) forebodes the potential application of GDY as an ultraviolet optical material. The outstanding NLA resulting in an ultraviolet waveband attests that the GDY nanosheets are veritable ultraviolet NLA materials, which have potential applications in ultraviolet optics. Our study broadens the application scopes of nanomaterials.